MODEL OF PREDICTING FINANCING AMOUNTS THROUGH THIRD-PARTY FUNDS, LIABILITIES, AND EQUITY - Widiawati; Mudzakir, Ahmad; Suteja Wira Dana Kusuma (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2025)
The amount of financing is a means for banks to gain profits. However, financing cannot be done haphazardly because of the risk of financing problems. For this reason, special considerations are needed in determining the amount of financing at the bank. This research aims to analyze the model for determining the amount of financing through third party funds, liabilities and equity. This research is research using a quantitative paradigm with an associative approach to analyzing cause and effect relationships. Data analysis uses regression analysis, t test statistics, f test statistics and coefficient of determination. The results of the analysis show that third party funds have a positive and significant effect on the amount of financing with a coefficient of determination of 63.2%. Liabilities have a significant positive effect on the amount of financing with a coefficient of determination of 63.4%, while equity has a significant negative effect. With an accurate predictive model, bank management can develop more targeted financing strategies based on projections of available funds from third parties, liabilities, and equity, thereby optimizing resource allocation so that financing does not exceed the bank's liquidity capacity. The model results can provide insight into whether third parties or equity growth needs to be increased to encourage certain types of financing (e.g., MSME financing or mortgages).